Suture techniques during laparoscopic and robot-assisted partial nephrectomy: a systematic review and quantitative synthesis of peri-operative outcomes - Bertolo, Riccardo; Kriegmair, Maximilian (BJU international, 2019)
Objective To summarize the available evidence on renorrhaphy techniques and to assess their impact on peri-operative outcomes after minimally invasive partial nephrectomy (MIPN). Materials and Methods A systematic review of the literature was performed in January 2018 without time restrictions, using MEDLINE, Cochrane and Web of Science databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement recommendations. Studies providing sufficient details on renorrhaphy techniques during laparoscopic or robot-assisted partial nephrectomy and comparative studies focused on peri-operative outcomes were included in qualitative and quantitative analyses, respectively. Results Overall, 67 and 19 studies were included in the qualitative and quantitative analyses, respectively. The overall quality of evidence was low. Specific tumour features (i.e. size, hilar location, anatomical complexity, nearness to renal sinus and/or urinary collecting system), surgeon's experience, robot-assisted technology, as well as the aim of reducing warm ischaemia time and the amount of devascularized renal parenchyma preserved represented the key factors driving the evolution of the renorrhaphy techniques during MIPN over the past decade. Quantitative synthesis showed that running suture was associated with shorter operating and ischaemia time, and lower postoperative complication and transfusion rates than interrupted suture. Barbed suture had lower operating and ischaemia time and less blood loss than non-barbed suture. The single-layer suture technique was associated with shorter operating and ischaemia time than the double-layer technique. No comparisons were possible concerning renal functional outcomes because of non-homogeneous data reporting. Conclusions Renorrhaphy techniques significantly evolved over the years, improving outcomes. Running suture, particularly using barbed wires, shortened the operating and ischaemia times. A further advantage could derive from avoiding a double-layer suture.
Gesehen am 28.11.2019
First published: 14 September 2018